L’émergence des services environnementaux dans le droit international de l’environnement : une terminologie confuse - Marie Bonnin (Éditions en environnement VertigO, 2012)
This article shows that the recent appearance of the terms of ecosystem services and environmental services, like tools of conservation of the biodiversity, is not accompanied by clear definition nor even of a consensus on the term used.The plurality of existing names for these services reveals certain confusion and indicates a lack of consensus between environmental international agreements, international organizations, and national institutions.The first traces of this concept can be raised as of beginning of the year 90 at the same time in binding texts and not-binding texts. However in majority of the examples, the concept appears by the means of the texts adopted by conferences of the parties.This use of terms without consensus was regarded as problems by several conferences of the parties. Some decided to join an explanatory term to it, others questioned the interest of its use. This terminological amalgam calls a clarification, which should be a precondition to the development of this concept in law. A precise definition of the concepts of environmental and ecosystem services could be a first step towards a better apprehension of this concept and could allow a reasoned use of the environmental evaluation favorable to the conservation of the biodiversity.